ENDOPHYTIC MICROORGANISMS OF AROEIRA TREE AND THEIR POTENTIAL AS PRE-EMERGENT BIOHERBICIDE FOR WEEDS - Camargos, Ítalo Matteus Fernandes; Holanda, Luivânia Thamires Leite; Corrêa, Caline Cristine Cavalcante; Rodrigues, Tatiana Tozzi Martins Souza (Floresta, 2024)
The endophytic microbiota of native plants is still poorly understood, but their potential to produce bioactive compounds of interest for agriculture has registered an increasing number of articles. Environments such as the Dry Forest bring together characteristics that can harbor a diverse endophytic microbiota with metabolic particularities with potential to be explored. The objectives of this study were to isolate fungi and bacteria from aroeira leaves (Myracrodruon urundeuva Freire Alemão) situated at the Mata Seca National Park, Manga/MG; identify them through the sequencing of the ITS region and 16S rRNA gene, and evaluate the potential bioherbicidal effect of their metabolites on germination and vigor of Urochloa brizanthaCV. Piatã, Bidens pilosa L. and Stylosanthes sp. seeds. The genus Phomopsis was the most abundant in the capoeira tree, being found in 12 of the 19 isolated fungi. Phomopsis sp., Bacillus sp., and Brevilacillus sp. metabolites interfered with the vigor of the seeds, presenting a potential bioherbicidal effect.